2021
DOI: 10.3389/fpls.2021.710383
|View full text |Cite
|
Sign up to set email alerts
|

The Streptochaeta Genome and the Evolution of the Grasses

Abstract: In this work, we sequenced and annotated the genome of Streptochaeta angustifolia, one of two genera in the grass subfamily Anomochlooideae, a lineage sister to all other grasses. The final assembly size is over 99% of the estimated genome size. We find good collinearity with the rice genome and have captured most of the gene space. Streptochaeta is similar to other grasses in the structure of its fruit (a caryopsis or grain) but has peculiar flowers and inflorescences that are distinct from those in the outgr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 134 publications
0
11
0
3
Order By: Relevance
“…euAP2- like genes have two AP2 domains ( Kim et al, 2006 ), rather than the single domain found in FZP . In addition, nearly all genes in this group also have miR172 binding sites ( Seetharam et al, 2021 ) and miR172 expression opposes expression of AP2- like genes ( Figure 5A ). The AP2- like -miR172 interaction has been investigated for its role in specifying the number of florets per spikelet (e.g.…”
Section: Spikelet Bracts (Glumes) Expand Axillary Bud Growth Is Suppr...mentioning
confidence: 96%
See 1 more Smart Citation
“…euAP2- like genes have two AP2 domains ( Kim et al, 2006 ), rather than the single domain found in FZP . In addition, nearly all genes in this group also have miR172 binding sites ( Seetharam et al, 2021 ) and miR172 expression opposes expression of AP2- like genes ( Figure 5A ). The AP2- like -miR172 interaction has been investigated for its role in specifying the number of florets per spikelet (e.g.…”
Section: Spikelet Bracts (Glumes) Expand Axillary Bud Growth Is Suppr...mentioning
confidence: 96%
“…In wheat, the IDS ortholog is the domestication gene Q ( Seetharam et al, 2021 ), which is also regulated by miR172 ( Debernardi et al, 2017 ). The transition to forming glumes is particularly obvious in wheat because the glumes have prominent keels, shorter awns, and more sclerenchyma than lemmas.…”
Section: Spikelet Bracts (Glumes) Expand Axillary Bud Growth Is Suppr...mentioning
confidence: 99%
“…Our initial analysis encompassed genomes from eight Poaceae species. To ascertain the origin of the Exo70FX clade, we identified Exo70 clade members in the recently sequenced genomes of Streptochaeta angustifolia ( 46 ) and Pharus latifolius ( 47 ), which represent critical species at the boundary of the Poaceae family. In addition, we included Ananas comosus (pineapple; Poales, Bromeliaceae) ( 48 ) and Musa acuminata (banana; Zingiberales, Musaceae) ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…На разных этапах существования полиплоида потеря генов происходит с разной интенсивностью -как правило, на стадии неополиплоида идут многочисленные перестройки генома (Xiong et al, 2011;Buggs et al, 2012) В процессе фракционирования нео-и мезополиплоидных геномов разных видов, по комплектам сохранившихся в дуплицированном состоянии и оставшихся в единичных копиях генов геномы растений всех филогенетических ветвей оказываются различны, что может рассматриваться как причина морфологических различий между таксонами. Так, сильно измененные в сравнении с другими Poaceae колоски архаичной ветви Streptochaeta, по-видимому, появились после того, как геном Streptochaeta потерял одну из двух копий, влияющих на морфологию колоска генов fruitfull (ful) и leafy hull sterile1 (lhs1), дублированных у общего предка Poaceae и в дублированном состоянии сохранившихся у остальных злаков (Seetharam et al, 2021). Напротив, гены, кодирующие факторы транскрипции и влияющие на морфологию колоска frizzy panicle (fzp) и branched silkless1 (bd1) в геномах «продвинутых» злаков дуплицированы, а у имеющего особые по строению колоски архаичного Pharus latifolius сохранились только в одной копии (Ma et al, 2021).…”
Section: фракционирование генома и сегментная дупликация некоторых ге...unclassified
“…После дупликации исходный ген и его новообразованные копии могут сосуществовать в геноме десятки и сотни млн лет (Panchy et al, 104 Родионов А. В. Механизмы видообразования и прогрессивной эволюции 2016; Ma et al, 2021;Seetharam et al, 2021;Yuan et al, 2021). Судьба у новообразованных дочерних копий гена может быть разная.…”
Section: фракционирование генома и сегментная дупликация некоторых ге...unclassified